Portrait: Image of man and the origin of art (2021)
Sometimes, art theory addresses the same type of image from discursive disparity. This is the case of the portrait, whose imprecise definition complicates its conceptual and formal definition within the limits of the Western culture. Although this text does not intend to resolve doubts about one of the most significant questions in art—even the question of art, if portraits are born with it—it does attempt to show the difficulties in reaching an agreement on the conventions that define it, from its antecedents in Antiquity and its establishment in modern times, up to the advent of its contemporary crisis that some authors attribute to the saturation suffered by the image in mass society, and others, to the new artistic paradigm that is imposed from Impressionism onwards.